Development of E-Module as an Instructional Media for Students with Hearing Impairments - Iga Setia Utami; Setia Budi; Afdhil Hafid (Journal of Educational Science and Technology (EST), 2023)
This study aims to produce an adaptive learning media that students with hearing impairments can use to increase independence in learning activities. In this study, the validity of the developed media was also tested. This development research uses the Instructional Development Institute (IDI) model, which consists of three stages. The first stage is the definition stage, which contains problem identification and background analysis steps. The second stage is the development stage which includes the preparation of the initial form of the product, and the third stage is the evaluation stage. The research instrument used is a validation sheet consisting of content and media validation which is analyzed by the descriptive analysis technique. The results showed that 1) the e-module developed was very good in the content aspects, and 2) the e-module developed was good in the media aspect. Based on the study’s results, the e-module developed is valid for use as media for students with hearing impairments.